(untitled) (ModaPalavra e-periódico, 2011)
This study was constructed from connections between the topics: product design for clothing and human factors in the discipline of Design and Human Factors, of the Master Course in Design, in UniRitter. Initially, we want a deeper conceptual about fashion design, made by a literature review, and reflection about the use of design methods in design disciplines on higher education courses in fashion design. The main objective is to highlight the importance of considering human factors in the teaching of the projection of fashion products. As a result, we point to the need for research on teaching fashion projects and studies suggest that indicate the applicability of human factors in product design for garments.